Error Theories of Absence Causation Are Not (Yet) Adequately Motivated - Meadows, Phillip (JoLMA)
In this paper I consider the merits and motivations for eliminativist error theories of absence causation, such as those offered by Beebee, Varzi, and Mumford. According to such views, there is no causation by absence. Here I argue that, despite offering an alternative picture of the practice of citing absences as causes, these views are inadequately motivated. I consider and reject a range of arguments for error-theoretic approaches, including appeals to ontological economy, physicalism and the causal closure of the physical, as well as Mumford’s recent appeal to soft Parmenideanism. I also argue that the arguments in the literature which aim to show that causation by absence is conceptually problematic are less forceful than they might initially appear. The result is that there is no compelling reason yet why we should reject absence causation.